Axonal Spectrins: Nanoscale Organization, Functional Domains and Spectrinopathies - Liu, Cheng-Hsin; Rasband, Matthew Neil (Frontiers in Cellular Neuroscience, 2019)
Spectrin cytoskeletons are found in all metazoan cells, and their physical interactions between actin and ankyrins establish a meshwork that provides cellular structural integrity. With advanced super-resolution microscopy, the intricate spatial organization and associated functional properties of these cytoskeletons can now be analyzed with unprecedented clarity. Long neuronal processes like peripheral sensory and motor axons may be subject to intense mechanical forces including bending, stretching, and torsion. The spectrin-based cytoskeleton is essential to protect axons against these mechanical stresses. Additionally, spectrins are critical for the assembly and maintenance of axonal excitable domains including the axon initial segment and the nodes of Ranvier. These sites facilitate rapid and efficient action potential initiation and propagation in the nervous system. Recent studies revealed that pathogenic spectrin variants and diseases that protealyze and breakdown spectrins are associated with congenital neurological disorders and nervous system injury. Here, we review recent studies of spectrins in the nervous system and focus on their functions in axonal health and disease.